“Meraba” Pornografi di Ruang Kelas - Rita Gani (MediaTor (Jurnal Komunikasi), 2007)
Controversies spark everywhere when Playboy, an American franchise adult magazine, appeared in the market. Although Indonesians have experienced some important social transformations, such controversies marked the proof that there are still many conservatives among Indonesians who object a man-mag